Morphobiological description of deep-sea shark Etmopterus unicolor (Etmopteridae, Squliformes) from the waters at northeastern Japan - Vladimir N. Dolganov (Известия ТИНРО, 2015)
Morphological description is given for 27 specimens of shark Etmopterus unicolor caught off northeastern Japan in 1980. Counts for vertebras, teeth rows, and intestinal valves are presented, as well. The species biology is discussed.